A multicomponent microemulsion using rational combination strategy improves lung cancer treatment through synergistic effects and deep tumor penetration. (1st January 2017) - Qu, Ding; Guo, Mengfei; Qin, Yue; Wang, Lixiang; Zong, Bing; Chen, Yunyan; Chen, Yan
Abstract: Previously, we have developed a multicomponent-based microemulsion composed of etoposide, coix seed oil, and ginsenoside Rh2 (ECG-MEs). In this study, our goal was to validate the feasibility of ECG-MEs in lung cancer treatment and explore the mechanism underling the enhanced antitumor efficacy. The optimal weight ratio of ginsenoside Rh2 (G-Rh2) in ECG-MEs was determined as 3% (wt%), that was capable of forming the microemulsion readily with small particle size and high drug encapsulation efficiency. In cellular studies, the intracellular fluorescence of human non-small cell lung cancer (A549) cells treated with fluorescein isothiocyanate-labeled ECG-MEs (FITC/ECG-MEs) was significantly higher than that of various controls, leading to the obviously synergistic anticancer activities in cytotoxicity and in vitro cell apoptosis induction. The anticancer efficacy in vivo results showed that ECG-MEs markedly inhibited the growth of A549 tumor xenografts, potently induced tumor cells apoptosis, and obviously prolonged the survival time of mice. Of note, the mechanisms of enhanced anticancer efficiency were connected with the small size-mediated deep tumor penetration and increase in serum concentration of T helper 1 (Th1) cytokines. In summary, ECG-MEs exerting the rational drug combination strategy offers a solid evidence for lung cancer treatment, and has a promising potential for clinical application.